The Regulatory Roles of Chemerin-Chemokine-Like Receptor 1 Axis in Placental Development and Vascular Remodeling During Early Pregnancy - Zhang, Qingqing; Xiao, Zhonglin; Lee, Cheuk-Lun; Duan, Yong-Gang; Fan, Xiujun; Yeung, William S. B.; Chiu, Philip C. N.; Zhang, Jian V. (Frontiers in Cell and Developmental Biology, 2022)
Chemerin is an adipokine that regulates metabolism in pregnancy. An elevation of serum chemerin level is associated with pregnancy complications. Consistently, we demonstrated that the chemerin expression was increased in placenta of preeclamptic patients at deliveries. The G protein-coupled receptor chemokine-like receptor 1 (CMKLR1) mediates the actions of chemerin. The functions of the chemerin-CMKLR1 axis in maintaining pregnancy are still unknown. In this study, we demonstrated that CMKLR1 was expressed in the decidual natural killer (dNK) cells and chorionic villi of human. Chemerin suppressed the proliferation of the dNK cells in vitro. Specific antagonist of CMKLR1, α-Neta abolished the suppressive effect of spent medium from chemerin-treated dNK cells culture on extravillous trophoblast invasion. Activation of the chemerin-CMKLR1 axis promoted fusion and differentiation of human cytotrophoblast to syncytiotrophoblast in vitro. We generated Cmklr1 knockout mice and showed that the Cmklr1 deficiency negatively affected pregnancy outcome in terms of number of implantation sites, litter size and fetal weight at birth. Histologically, the Cmklr1 deficiency impaired formation of the syncytiotrophoblast layer II, induced enlargement of the maternal lacunae in the labyrinth, increased the diameter of the spiral arteries and increased trophoblast invasion in the decidua. The Cmklr1 deficient placenta also displayed an increased number of dNK cells and serum IL-15 level. In summary, the chemerin-CMKLR1 axis regulated placental development and spiral artery remodeling in early pregnancy.